Inclinations: Dancing Ramps, Disability, and Multiplicities through Research-Creation - Peers, Danielle; Sheppard, Alice; Eales, Lindsay; Schenk, Abbie (Art/Research International, 2022)
Inclinations is an audio-described, 7-minute, site-specific, disability dance on film followed by a video discussion between three of the disabled artist-researchers. Throughout this project, we embraced a research-creation methodology to engage with the research question: How can we fully embed intersectional disability justice, not only as a theoretical lens, but also, as a methodological imperative? This work centres the concepts of disability culture and disability generativity, and purposefully diverges from more popular traditions of physically-integrated dance in favour of disability dance. We demonstrate and discuss how this choice—alongside various filmic practices—seeks to decentre the ableist gaze, normalizing narratives, and the ubiquitous non-disabled referent. Other methodological considerations enacted and discussed in this work include centring access aesthetics, consent, care, disability justice principles, and questions of power in every aspect of the creation process.